Mobility of the human foot’s medial arch helps enable upright bipedal locomotion - Welte, Lauren; Holowka, Nicholas B.; Kelly, Luke A.; Arndt, Anton; Rainbow, Michael J. (Frontiers in Bioengineering and Biotechnology, 2023)
Developing the ability to habitually walk and run upright on two feet is one of the most significant transformations to have occurred in human evolution. Many musculoskeletal adaptations enabled bipedal locomotion, including dramatic structural changes to the foot and, in particular, the evolution of an elevated medial arch. The foot’s arched structure has previously been assumed to play a central role in directly propelling the center of mass forward and upward through leverage about the toes and a spring-like energy recoil. However, it is unclear whether or how the plantarflexion mobility and height of the medial arch support its propulsive lever function. Here we show, using high-speed biplanar x-ray, that regardless of intraspecific differences in medial arch height, arch recoil enables a longer contact time and favorable propulsive conditions at the ankle for walking upright on an extended leg. This mechanism may have helped drive the evolution of the longitudinal arch after our last common ancestor with chimpanzees, who lack this plantarflexion mobility during push-off. We discovered that the generally overlooked navicular-medial cuneiform joint is primarily responsible for arch recoil in human arches, suggesting that future morphological investigations of this joint will provide new interpretations of the fossil record. Our work further suggests that enabling longitudinal arch recoil in footwear and surgical interventions may be critical for maintaining the ankle’s natural propulsive ability.